(untitled) (New York, 1999)
Guidelines, properties, and specifications for a broad range of wood structures--new construction and the rehabilitation of older buildings. Includes many design examples and tables of design data for columns, beams, fasteners and connectors, trusses, diaphragms and shearwalls, structural panel products, arches and domes, and foundations. Discusses the accepted standards of the industry (including commercial lumber standards) and describes fire-resistive design and sound control
Keywords: Building, wooden